Transformative Learning: Narrative Analysis or Analysis of Narratives? - Jane Robertson; James Lappeman (International Journal of Qualitative Methods)
This study used narrative inquiry to observe the occurrence and nature of transformative learning in a management development programme. The methodology of using participant narratives comes with several challenges for the researcher to remain true to the expressed story. Thus, by adding another step in moving from narrative analysis to the analysis of narratives, this paper provides a novel perspective on qualitative research of this nature. The application of McCormack’s four lenses of process, context, moments and language provided additional insight into understanding the participants’ lived experience of transformative learning. The use of thematic maps and thematic networks were also incorporated to create visual representations of the themes, and to keep the story intact. These too are unfamiliar in most versions of narrative analysis.